The renewal of the literary communication contract of "Conto de Escola": characteristics and implications (Gragoatá, 2020)
This article aims at analyzing how the redefinition of the subjects of the narrative staging, channel, and semiological codes determines the renewal of the literary contract of the short story "Conto de Escola" in its 2002 reprint by Cosac Naify publishers, taking into account the Semiolinguistic Discourse Analysis Theory and, in a subsidiary way, the studies of editorial paratexts and visual forms. The Machadian short story, originally published in 1884, was reprinted, in a book of the same name, as a verbal-visual hybrid text by the publisher's initiative and the work of Nelson Cruz, who authored the illustrations and the editorial project. The most relevant implications of this process of renewal of the literary contract are the amplification of the effects of meaning and, more particularly, the intensification of the pathemic effects as a result of the word-image interaction, which is inserted in a material and discursive mise-en-scène, organized by the editorial paratexts. This results in inscribing children as target readers, unlike previous contracts, which now allows for the book under analysis to be identified as potential literature for children.------------------------------------------------------------------------------------------A RENOVAÇÃO DO CONTRATO DE COMUNICAÇÃO LITERÁRIO DE “CONTO DE ESCOLA”: CARACTERÍSTICAS E IMPLICAÇÕESO objetivo deste artigo é analisar, com base na Teoria de Análise Semiolinguística do Discurso, e, subsidiariamente, nos estudos dos paratextos editoriais e das formas visuais, como a redefinição dos sujeitos da encenação narrativa, do canal e dos códigos semiológicos determina a renovação do contrato literário de “Conto de escola” na reedição de 2002 da Cosac Naify. O conto machadiano, publicado originalmente em 1884, foi reeditado em livro homônimo como um texto híbrido verbo-visual pela iniciativa do editor e pelo trabalho de Nelson Cruz, autor das ilustrações e do projeto editorial. As implicações mais relevantes desse processo de renovação do contrato literário são a amplificação dos efeitos de sentido e, mais particularmente, a intensificação dos efeitos patêmicos em decorrência da interação palavra-imagem, inserida em uma mise-en-scène material e discursiva organizada pelos paratextos editoriais. Isso tem como consequência a inscrição da criança como leitor destinatário não previsto nos contratos anteriores, o que permite que o livro objeto de análise seja identificado com a literatura de potencial destinação infantil.---Original em inglês.